2012
DOI: 10.1148/radiol.12112478
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel Incoherent Motion Diffusion-weighted Imaging in Nonalcoholic Fatty Liver Disease: A 3.0-T MR Study

Abstract: D is significantly decreased in steatosis. The reduction in D* reflects decreased liver parenchymal perfusion in steatosis. Therefore, steatosis can affect diffusion parameters obtained with IVIM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
143
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(160 citation statements)
references
References 40 publications
14
143
3
Order By: Relevance
“…FNH contains bile ducts; therefore, after taking up a hepatocyte-specific contrast agent, delayed biliary excretion is possible. Lastly, the background for state of the organ, such as the liver fat content, fibrotic tissue fraction, and even chronic disease such as pancreatitis, could have considerable influences on the measurement of parameters (7,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…FNH contains bile ducts; therefore, after taking up a hepatocyte-specific contrast agent, delayed biliary excretion is possible. Lastly, the background for state of the organ, such as the liver fat content, fibrotic tissue fraction, and even chronic disease such as pancreatitis, could have considerable influences on the measurement of parameters (7,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Various fitting algorithms have been used to determine IVIM parameters, including asymptotic fitting (9)(10)(11)(12)(19)(20)(21)24,41,45,46,48,51,53), nonlinear least square (usually Levenberg-Marquardt) fitting (23,42,47,52,54,55), and Bayesian fitting (15,22,40,43,50). Current review cannot draw conclusion which one is better than others, nor can the mean values be compared (Figure 8).…”
Section: Image Post-processing Methods For Ivim Parametersmentioning
confidence: 99%
“…With IVIM technique, Luciani et al reported that Dfast was significantly reduced in the liver fibrosis compared with those in the healthy liver group, but there was no significant difference between Dslow and PF measurements in the healthy liver (n=25) and the liver fibrosis (n=12) groups (11). Guiu et al (9) reported that Dslow and Dfast were significantly lower in steatotic compared with nonsteatotic livers; however, PF was significantly higher in steatotic compared with nonsteatotic livers. In another study, Patel et al (12) reported that the value of Dslow, PF and Dfast in liver cirrhosis were lower than non-cirrhosis liver; however, no further grading was performed within their liver cirrhosis subjects as only three patients had histopathology data.…”
Section: Ivim For Liver Fibrosis Evaluationmentioning
confidence: 98%
See 2 more Smart Citations